A comprehensive review of value-added CO2 sequestration in subsurface saline aquifers - Kumar, S. (Elsevier B.V., 2020)
This paper comprehensively reviews CO2 sequestration process in saline aquifers. The storage mechanisms including structural, residual, solubility, and mineral trappings are assessed along with a discussion of their relative contributions, and their key parameters and optimisations. In view of storage security and capacity, effects of rock and fluid properties and reservoir conditions together with injection strategies are discussed. Furthermore, CO2 storage site selection is investigated followed by an evaluation of the different measurement, monitoring and verification methods to mitigate the risk of leakage. Field examples with key learnings are also presented to help engineers with sustainable development of storage projects. Â© 2020 Elsevier B.V.